Organizing, training and equipping the Air Force for crises and lesser conflicts - Builder, Carl H., 1931-1988; Karasik, Theodore William; Rand eBooks (Santa Monica, CA : RAND, 1995)
Operations short of war, one of three basic responsibilities of the U.S. armed services, are increasingly consuming the attention and resources of U.S. military forces around the world, in such places as Bosnia, Somalia, Haiti, Rwanda, and Kuwait. The most stressing of these operations are nonroutine international crises and conflicts, particularly those that might lead to U.S. combat operations short of war. These situations have, at times and for some specialized capabilities, stressed the forces to exhaustion or failure. More generally, they have encroached upon the training and readiness of the forces, leading to a public debate as to whether such assignments are a "proper" use of U.S. military power. This report explores where, why, and how operations short of war are stressing the forces, particularly the aerospace forces, and how those stresses upon USAF capabilities might be relieved by changes in Air Force organization, training, and equipment.
"Project Air Force."
Includes bibliographical references (p. 89-93).
Also available on the internet via WWW in PDF format.
Keywords: United States. -- Air Force -- Operational readiness; Air defenses -- United States -- Planning; Low-intensity conflicts (Military science) -- Planning; Electronic books